Preparation and characterization of micellar nanoparticles using crude saponins from five Congolese plant species - Pathy B. Lokole; Nadège K. Ngombe; Dave I. Motomba; Justin B. Safari; Michel K. Mpuza; Rui W.M. Krause; Paulin K. Mutwale; Christian I. Nkanga (Pharmaceutical Science Advances)
Nanoparticles (NPs) have significantly advanced medical applications, including drug delivery, immunotherapy, vaccines, and diagnostics. This versatility is partly due to the potential of tailoring NPs from multiple sources. Notably, saponins, amphiphilic plant metabolites, have shown great promise in NP formulation. This study explored the development of micellar NPs using saponin crude fractions (SCFs) extracted from five Congolese plant species: Millettia laurentii, Penthaclethra eetveldeana, Schwenckia americana, Musa paradisiaca, and Musa sapientum. Plant materials were subjected to histological examination through optical microscopy, while phytochemical analyses by thin-layer chromatography confirmed the presence and predominance of saponins in the SCFs. We used a phthalocyanine-isoniazid hybrid (Pc-INH) as a hydrophobic probe to determine the critical micellar concentrations of SCFs and explore the feasibility of developing cost-effective saponin-based micelles (SBMs). Phytochemical screenings indicated saponins in the extracted SCF and other metabolites like flavonoids, phenolic acids, and anthocyanins. Dynamic light scattering and transmission electron microscopy analyses revealed the formation of nano-sized particles, particularly noting SBMs from P. eetveldeana with notable dimensions (157 ​nm, PDI of 0.27, and ZP of −4.01 ​mV) and spherical shape. The micelles from M. laurentii exhibited superior encapsulation efficiency for Pc-INH (55%) compared to control micelles formulated from pure saponin (33%). In vitro tests showed that M. paradisiaca SBMs have the best safety profile for red blood cells, with a 10% hemolysis rate compared to a 150% rate for bulk SCFs. However, there is a significant difference between SCFs and SBMs (p ​< ​0.0001). The release profiles of M. paradisiaca SBMs show a pH-dependent relationship, suggesting potential for stimuli-responsive drug delivery. This work lays the foundation for leveraging plant-derived crude saponins in nanotechnology, emphazising their encapsulation efficiency, controlled release potential, and biocompatibility, paving the way for the cost-effective production of high-value biomedical NPs.